Biodiversity and Genetic Relationships to the Species for the genus Gladiolus L. (Iridaceae) Wild Growing in Iraq Using RAPD-PCR Technique - A.Farman, Areej; N. Aboud, Mazin (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study observed the genetic diversity and relationships among 4 species belonging to genus Gladiolus L. , by using the Random Amplified Polymorphic DNA (RAPD) technique , the study includes extraction of genomic DNA from the dray leaves by using commercial kit . 4 random primers used the produced of many polymorphic bands among the 4 species , it was also possible to fined the DNA fingerprint of all studied species.Through the appearance of a number of bands that were unique to each species.Genetic distances ranged from 0.10 to 0.86, and used cluster analysis were performed to construct dendrogram.Cluster analysis grouped the 4 species Into tow main clusters depending on their ancestor and their morphological and anatomical traits. Depending on the results of this study and other such as anatomical and palynologycal studies we can record a new species in Iraq belonging to genus Gladiolus, it is G. anatolicus.